KEBIJAKAN PEMERINTAH DESA DALAM PEMBERDAYAAN MASYARAKAT PADA PROGRAM BUMDES - Yulianus Nardin (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Abstract: The problem of inequality which is a reality in development requires solving with partiality to the community through the Empowerment program, thus the role the government and the community are urgently needed in resolving economic inequalities, This underdevelopment can be formulated in an empowerment program policy concept by government through the BUMDes Program, as an effort to improve the economic welfare of the community. Potential / excellence is driven by the Village Government. This type of research uses the method qualitative approach, Pesanggrahan Village, Batu District, Batu City is the research location. Results Research shows that the role of village government in community empowerment in the Program BUMDes. Pesanggrahan Village, Batu District, Batu City in accordance with the strategy program empowerment which includes the development of human resources, institutional development groups, fertilizing public (private) capital, productive business development, and supply appropriate information has not been fully effective, due to the development process group institution that is still in the process of transition improvement, in this case hydroponic agriculture experiencing traffic jams in the special management staff, which resulted in no hydroponic farming manicured.Keywords: Government Policy, Community EmpowermentAbstrak: Masalah Kesenjangan yang merupakan kenyataan dalam pembangunan memerlukanpemecahan dengan pemihakan pada masyarakat melalui program Pemberdayaan, demikian peranpemerintah dan masyarakat sangat diperlukan dalam menyelesaikan kesenjangan ekonomi,keterbelakangan ini dapat di rumuskan dalam satu konsep kebijakan program pemberdayaan olehpemerintah melalui Program BUMDes, sebagai upaya meningkatkan kesejahteraan ekonomi masyarakat.Potensi/keunggulan digerakkan oleh Pemerintah Desa. Jenis penelitian ini menggunakan metodependekatan kualitatif, Desa Pesanggrahan, Kecamatan Batu, Kota Batu merupakan lokasi penelitian. HasilPenelitian menunjukkan bahwa Peran pemerintah desa dalam pemberdayaan masyarakat pada ProgramBUMDes. Desa Pesanggrahan, Kecamatan Batu, Kota Batu sesuai dengan program strategipemberdayaan yang meliputi pengembangan sumber daya manusia, pengembangan kelembagaankelompok, pemupukan modal masyarakat (swasta), pengembangan usaha produktif, dan penyediaaninformasi tepat guna belum sepenuhnya berjalan efektif, dikarenakan pada Proses pengembangankelembagaan kelompok yaitu masih dalam proses transisi perbaikan, dalam hal ini pertanian hydroponicmengalami kemacetan pada staf khusus pengelola, yang mengakibatkan pertanian hydroponic tidakterawat.Kata Kunci: Kebijakan Pemerintah, Pemberdayaan Masyarakat